CYSTIC LEIOMYOMA PRESENTING AS AN OVARIAN CYST: Cytic Leiomyoma - Mushtaq, Huma; Jamal, Shahid; Mubarik, Azhar; Sarwar, Urwa (Pakistan Armed Forces Medical Journal, 2009)
INTRODUCTION Leiomyomas are the commonest smooth muscle tumour in the uterus. Not only do they occur at varied sites but they show multiple types of degenerative alterations such as hyalinization, myxoid, carneous (red or hemorrhagic), fatty, calcific and cystic changes [1]. Sometimes cyst may be so large that it can mimic other cystic malignancies. One such case is reported